Kepastian Hukum Penerapan Pajak Air Permukaan (PAP) Di Pemerintahan Daerah Sumatera Utara - Tuti Sukmawati; Khalimi Khalimi; Sartono Sartono (JOURNAL of LEGAL RESEARCH, 2022)
The Surface Water Tax (PAP) is one source of regional income. There are disputes and uncertainties that occur at PT. Indonesia Asahan Aluminum or PT. INALUM which has a different perception/understanding in determining the basic water price and the difference in determining the basic water price compared to other similar companies, causing legal uncertainty. The research method used is a normative juridical method, namely library law research that emphasizes secondary data research. The research approach used is a case study of the decision no. PUT-105234.06/2015/PP/M.IIA 2018. This research was conducted to examine how clear legal certainty is in the PT. INALUM and the Regional Government of North Sumatra Province. Based on research on legal certainty, the Regulation of the Governor of North Sumatra Number 24 of 2011 is not clear, causing problems with different calculations, so it is recommended to immediately follow up on the study conducted by BPKP regarding the surface water tax rate for electricity generation for its own purposes.